Intergenerational Environmental Justice as a Human Rights Fulfillment - Ferina Ardhi Cahyani (Jurist-Diction, 2022)
AbstractEnvironmental issues are currently getting a lot of attention both in Indonesia and internationally. The rise of irresponsible deforestation, air pollution in big cities, irresponsible industries for the waste produced, the use of goods that are difficult to decompose, and so on are examples of how bad environmental conditions are today. In fact, the guarantee for a healthy environment is stated in the 1945 Constitution of the Republic of Indonesia. In addition, the environment is also regulated separately in Law Number 32 of 2009 concerning Environmental Protection and Management. The principle of sustainable development should be applied in carrying out all activities that affect the environment. However, the present generation who are responsible for the availability and preservation of natural resources for future generations so that intergenerational justice can be realized.Keywords: Intergenerational Justice; Environmental justice; Human Rights; Sustainable Development.